Social transformations in the city of Constantine at the beginning of the French colonialism (1830-1845): An approach of marriage and divorce contracts according to Maliki court records - BOULEDJOUIDJA , Souad (La Revue d’Histoire Méditerranéenne, 2024)
This study aims to explore a range of issues that permeate various aspects of daily life, with a particular focus on social and living conditions within Constantine. By examining the shifts engendered by political and economic influences under two distinct regimes—the Ottoman rule and the French occupation—the research utilizes marriage and divorce contracts as key indicators of social stratification. These documents, which detail individual incomes, property holdings, financial statuses, and class disparities, are sourced from the Maliki court records of Constantine, housed in the provincial archives. Through these historical records, this study aims to vividly reconstruct and portray the lived experiences of that era. In this study, we relied on the historical descriptive curriculum as well as the analytical and statistical curriculum for what the nature of the topic required. Entry into the city. This is confirmed by the documents of divorce contracts, especially in the transitional period, whether they relate to marriage conditions or to changes in social structure through the movement of families from within the city to outside, whether definitively or temporarily.